A case of battered wife - Ahmed, KS; Begum, A; Alamgir, M; Al Masud, M A (Bangladesh Journal of Medical Science, 2012)
The use of corrective force against the wife is still rife in all cultures and even socially acceptable in some culture. Domestic violence is still common in our society. We report a case of 20 years old woman who admitted into OCC of DMCH through emergency department owing to be assaulted by her husband. This case is exceptional one because the injuries inflicted upon her were over the middle of the forehead and clean cut in nature, though non fatal. Awareness and education is needed to stop this social stigma DOI: http://dx.doi.org/10.3329/bjms.v11i3.11736 Bangladesh Journal of Medical Science Vol. 11 No. 03 July12